2012
DOI: 10.1128/jcm.06214-11
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Type-Specific Prevalence in Women with Cervical Intraepithelial Neoplasm in Western China

Abstract: Human papillomavirus (HPV) type-specific prevalence was studied in 600 cases of cervical intraepithelial neoplasm in western China by GenoArray test. HPV-16 and -58 were the most prevalent types, with prevalences of 37.8% and 21.8%, respectively. HPV-18 and -45 were uncommon types. The results show different type distributions from that of other regions, which is important evidence for the selection of future genotypes in HPV vaccines in western China. Cervical carcinoma is one of the most common malignancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 12 publications
(10 reference statements)
1
19
0
Order By: Relevance
“…However, the HPV GenoArray Diagnostic Kit is an alternative technique for studies conducted in resource-limited laboratories because the cost of the HPV GenoArray Diagnostic Kit is lower than that of the Linear Array HPV Genotyping Test and the hybridization time is also lower (Li et al, 2012; Liu et al, 2010). Moreover, the HPV GenoArray assay can distinguish and identify HPV 52, which is one of the most common high-risk HPV genotypes in women in eastern and southeastern Asia (Sukvirach et al, 2003; Takehara et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the HPV GenoArray Diagnostic Kit is an alternative technique for studies conducted in resource-limited laboratories because the cost of the HPV GenoArray Diagnostic Kit is lower than that of the Linear Array HPV Genotyping Test and the hybridization time is also lower (Li et al, 2012; Liu et al, 2010). Moreover, the HPV GenoArray assay can distinguish and identify HPV 52, which is one of the most common high-risk HPV genotypes in women in eastern and southeastern Asia (Sukvirach et al, 2003; Takehara et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned study conducted in Urumqi, Xinjiang, found that the HR-HPV genotypes HPV-16, HPV-58, HPV-52 and HPV-18 accounted for 6.03, 2.56, 1.23 and 1.05% of all cases, respectively [18]. Another investigation, performed in Yunnan, China, revealed that the five most prevalent HR-HPV genotypes were HPV-16 (3.4%), HPV-56 (1.7%), HPV-58 (1.4%), HPV-33 (1.2%) and HPV-52 (0.88%), with an HPV-18 prevalence of 0.8% [11]. In both of these prior studies, the HPV-82 genotype was also detected; in our study, only one sample infected with the HPV-82 genotype was found.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Qujing of Yunnan Province, Southwest China, demonstrated that the five most prevalent HR-HPV genotypes in this region were HPV-16 (3.4%), HPV-56 (1.7%), HPV-58 (1.4%), HPV-33 (1.2%) and HPV-52 (0.88%) [10]. However, another study conducted on 600 patients with cervical intraepithelial neoplasm in Western China indicated that HPV-16 and HPV-58 were the most prevalent types of HPV, with prevalences of 37.8% and 21.8%, respectively, and that HPV-18 and HPV-45 were uncommon [11]. Considering that the distribution of HPV genotypes may greatly differ according to geographic region [11], largescale investigations in different regions are still needed.…”
Section: Bosnian Journal Of Basic Medical Sciences Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Only 6% of women were willing to pay more than US $300 for the vaccine. and safety of the vaccines, cost-effectiveness of cervical cancer prevention and control strategies Sexual behavior of the population, and knowledge and attitudes towards the vaccines and HPV-related diseases are also important (46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). In China, the prevalence of HPV 16 and 18, which are prevented by the current vaccines, is generally high, while there is a huge geographic diversity of the prevalence of oncogenic HPV types.…”
Section: Limitationsmentioning
confidence: 99%